1994
DOI: 10.1103/physrevb.50.831
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of amorphous hydrogenated carbon. I. A high-resolution neutron-diffraction study

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Other smaller peaks between 1.7 and 2.2 Å belong to correlations in the second coordination shell associated with H-C-H and C-C-H bonds. These small features are in a good agreement with experimental observations [54]. Fig.…”
Section: From A-c To A-c:hsupporting
confidence: 91%
“…Other smaller peaks between 1.7 and 2.2 Å belong to correlations in the second coordination shell associated with H-C-H and C-C-H bonds. These small features are in a good agreement with experimental observations [54]. Fig.…”
Section: From A-c To A-c:hsupporting
confidence: 91%
“…For both samples, the combined CC and CN first neighbor peak is at 1.43 Å, which is shorter than that obtained for CC nearest neighbors in a-C:H samples. 31,33 This is due to the presence of CN and NN bonds, which are shorter than the expected C-C and C‫ס‬C bonds, and therefore the average network neighbor bond distance observed for these a-C:N:H samples, where the correlation peaks overlap, appears shorter. The CH and NH correlations are observed as a dip in the data at ∼1 Å.…”
Section: B Neutron Diffractionmentioning
confidence: 89%
“…Building on our work on a-C:H 31,32 and earlier studies on a-C:N:H, 33,34 we present complementary neutron diffraction, inelastic neutron scattering and infrared spectroscopy data for a-C:N:H samples, with compositions of 3 and 7 at.% nitrogen, which will be used to provide additional insight into the carbon, nitrogen, and hydrogen bonding environments present. In particular, we examine the effects of nitrogen incorporation on the atomic-scale structure of the material with reference to the use of ammonia, NH 3 , as the source of nitrogen, and a supplementary source of hydrogen, in the precursor gas.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…From electronic structure calculations it has been suggested that the structure of a-C:H is composed of graphitic clusters of fused rings in an sp 3 matrix 5,6 and some experimental observations have tended to support this idea. [7][8][9][10][11][12][13][14] However this view has been challenged in a recent series of papers, [15][16][17][18] whose authors interpret their results to mean that the sp 2 bonds are olefinic ͓olefinic, hydrocarbon containing a carbon-carbon double bond, the bond is localized; aromatic (benzoic), hydrocarbon containing a phenyl ring, the bonds are delocalized around the ring; graphitic, graphitelike structure, the bonds are delocalized over an area͔ and not graphitic or benzoic. An earlier work also found localization of electrons.…”
Section: Introductionmentioning
confidence: 99%